Reconocimiento, transmisión y hospederas de patógenos virales del maracuyá (Passiflora edulis Sims) en Colombia - Chavez, B.; Varón de Agudelo, Francia; Morales, Francisco José; Castaño, M.; Arroyave, José A.; Gálvez E., Guillermo E. (1999)
One of the principal produdbon problems of passionfruit (Passiflora edulis) in the Cauca Valley and other departments of Colombia is the presence of virai pathogens, mainly a potyvirus and a tymovirus. These pathogens limit plants growth, reduce yields and productive life of infected plants. Due to the importance of this fruit crop in Colombia, an investigation was initiated to generate information on the geographical distribution, transmission, host range and indicators plants of the viral pathogcns. For this survey, 122 passionfruit production fields were visited in 11 departments of the country a total of 340 samples with apparent viral symptoms, were collected and used to mechanically inoculate test plants under greenhouse conditions. The viral pathogens were also graft-transmitted to passionfruit and other species. Valle, Caldas and Meta were the departments with higher disease incidence and severity. Mechanical inoculation and graft-transmission tests resulted in 17 and 30% transmission respectively. The most frequent symptoms were veinclearing, mosaic and chlorotic spots. Seven varieties of wild and cultivated passifloras inoculated by grafting were susceptible to the viral pathogens, inducing symptoms similar to those observed in the field. Inoculated granadilla, (P. ligularis), plants readed with foliar malformation and purpling of vein. 14 plants species were inoculated, inducing leguminoseae, solanaceae and chenopodiaceae, induceing systemic symptoms in Phaseolus vulgaris var. Black Turtle Soup B, Black Turtle Bush and Glycine max ICA L-186 vein necrosis, blisters and mosaic. In Physalis floridana an interveinal chlorosis was observed. Biological transmission experiments with the aphid Aphis gossypii, resulted in 27% incidence of infected plants, shows blistering and mosaic symptoms. The chrysomelid beetles Diabrotica sp., Cerotoma sp. and Colaspis sp. did transmit any virus. Seed transmission tests using more than 2000 seed originating from fruits colleted from diseased passionfruit plants. Their susceptible hosts included Passiflora foetida, P. cerulata, P. caerulea, P. adenopoda and Passiflora sp. (Chulupa) in addition to the cultivated passifloraceae.